BRIONY’S GUILTY FEELING AND HER ATONEMENT IN IAN MCEWAN’S ATONEMENT (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
BRIONY’S GUILTY FEELING AND HER ATONEMENT IN IAN MCEWAN’S ATONEMENT Lailatul Fitriya English Literature Study Program, Faculty of Languages and Arts, Surabaya State University lailafitriya71@yahoo.co.id Drs. Much. Khoiri, M.Si English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Much_choiri@yahoo.com Abstrak Perasaan bersalah dan taubat adalah hal yang ditunjukkan oleh seseorang ketika mereka membuat kesalahan atau dosa. Ian McEwan adalah salah satu penulis yang menulis sebuah novel tentang perasaan bersalah dan taubat. Penelitian ini bertujuan untuk menggambarkan perasaan bersalah dan taubat dari karakter utama. Dengan menggunakan teori-teori yang relevan, studi ini menganalisis kutipan-kutipan dari dalam novel yang mewakili perasaan bersalah dan taubat sebagai sumber data. Hasil analisis menunjukkan bagaimana perasaan bersalah Briony yang menyebabkan dirinya sebagai karakter utama melakukan taubat, perasaan bersalah tersebut dapat digambarkan dalam tiga jenis. Pertama, perasaan bersalah Briony yang digambarkan ketika dia menyadari kesalahannya dan dia merasa bahwa dia melakukan hal yang salah. Kedua, perasaan bersalah Briony yang digambarkan ketika dia melakukan hal yang baik. Ketiga, digambarkan ketika dia membuat permintaan maaf dengan mengatakan kebenaran yang sesungguhnya. Setelah perasaan bersalah ketiga muncul, dia ingin mengadakan taubat atas kesalahan yang dilakukan. Berdasarkan semua perasaan bersalah dalam hidupnya, ia kemudian mencoba untuk bertaubat dengan membuat cerita fiksi antara Robbie dan Cecilia. Sebagai novelis, ia menulis sebuah fiksi yang memiliki cerita bahagia antara Robbie dan Cecilia, karena dia menyadari tentang rasa bersalahnya yang telah membuat Robbie dan Cecilia menderita sampai akhir hayat tanpa bisa memenuhi cinta mereka berdua. Kata kunci: Rasa bersalah dan taubat Abstract Guilty feeling and atonement are the thing which have been showed by the people when they make a guilt or sins. Ian McEwan is the one of the writers that wrote a novel about guilty and atonement. This study aimed to depict a guilty feeling and an atonement of the main character. By using relevant theories, the study analyses the data for example, quotation from the novel that represent guilty feeling. The result of analysis shows how Briony’s guilty feeling depicted in the atonement can be described in three kinds. First, Briony’s guilty feeling is depicted when she realized of her guilt and she felt that she did a wrong thing. Second, Briony’s guilty feeling depicted when she did a good thing. Third is depicted when she made an apology by telling the fact. After the third guilty feeling passed, she wanted to make atonement. Based on all her guilty feeling in her life, she then tried to make atonement by making a fiction of Robbie and Cecilia. As a novelist, she wrote a fiction that has happy ending between Robbie and Cecilia, because she realized about her guilt that has made Robbie and Cecilia get suffered to death without being able to fulfil their love. Key words: Guilty feeling and atonement INTRODUCTION As in a general world, there is something that is always different in each side, good and bad is opposite one. In those two actions, there are consequences that will automatically happen in our live. Such an aphorism said that